Social Entrepreneurship Research: Past Achievements and Future Promises - Saebi, Tina; Foss, Nicolai J.; Linder, Stefan (Journal of Management, 2019)
The past decade has witnessed a surge of research interest in social entrepreneurship (SE). This has resulted in important insights concerning the role of SE in fostering inclusive growth and institutional change. However, the rapid growth of SE research, the emerging nature of the literature, and the fact that SE builds on different disciplines and fields (e.g., entrepreneurship, sociology, economics, ethics) have led to a rather fragmented literature without dominant frameworks. This situation risks leading to a duplication of efforts and hampers cumulative knowledge growth. Drawing on 395 peer-reviewed articles on SE, we (1) identify gaps in SE research on three levels of analysis (i.e., individual, organizational, institutional), (2) proffer an integrative multistage, multilevel framework, and (3) discuss promising avenues for further research on SE.